Recent Advances of Intraocular Lens Materials and Surface Modification in Cataract Surgery - Luo, Chenqi; Wang, Hanle; Chen, Xinyi; Xu, Jingjie; Yin, Houfa; Yao, Ke (Frontiers in Bioengineering and Biotechnology, 2022)
Advances in cataract surgery have increased the demand for intraocular lens (IOL) materials. At present, the progress of IOL materials mainly contains further improving biocompatibility, providing better visual quality and adjustable ability, reducing surgical incision, as well as dealing with some complications such as posterior capsular opacification (PCO) and ophthalmitis. The purpose of this review is to describe the research progress of relevant IOL materials classified according to different clinical purposes. The innovation of IOL materials is often based on the common IOL materials on the market, such as silicon and acrylate. Special properties and functions are obtained by adding extra polymers or surface modification. Most of these studies have not yet been commercialized, which requires a large number of clinical trials. But they provide valuable thoughts for the optimization of the IOL function.